The Role of Social Institutions for Tourist Attractiveness Development in Respect of Russian Cultural and Historical Heritage - ROGACH, Olga Vladimirovna; FROLOVA, Elena Victorovna; RYABOVA, Tatyana Mikhailovna; KABANOVA, Elena Evgen'evna (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).21, 2017)
In modern conditions the cultural and historical heritage is the main component of territory tourist attraction. The acquaintance with historical objects is one of the most significant motives for cultural and cognitive travel planning. The introduction of cultural and historical heritage objects into economic activities and the development of cultural tourism is the most demanded trend in the whole world. The purpose of the study is to analyze the role of social institutions that determine the values of historical and cultural heritage perception by Russian society. The conducted research allowed to conclude that the state, education, religion and mass media act as traditional institutional structures in Russian society that provide the regulation of the value orientations among Russian citizens. The article determined the main dysfunctions in the process of institutional conditions development for the preservation and perception of cultural and historical heritage. The key ones are the following ones: the ineffectiveness of socio-cultural tendency planning and programming, the commercialization of historical and cultural heritage, an inadequate financial support, a low level of population awareness concerning the tourist potential of Russian territories, an inadequate elaboration of educational programs that generate interest in cultural and historical heritage and in internal tourism. According to respondents, education should become the key institution that provides the development, consolidation and translation of values concerning historical and cultural heritage by Russian society.